2013
DOI: 10.1007/s10802-013-9746-8
|View full text |Cite
|
Sign up to set email alerts
|

Reward Dysregulation and Mood Symptoms in an Adolescent Outpatient Sample

Abstract: Research on bipolar spectrum disorders (BPSD) in adolescence has burgeoned in the last decade, but continued work is needed to identify endophenotypic markers associated with illness onset and course. The present study examined reward dysregulation – measured via the behavioral activation system (BAS) – as one putative marker of BPSD in adolescence. A diverse group of 425 outpatient adolescents between 11–17 years of age (52% male) completed the Behavioral Inhibition and Activation Scale (BIS-BAS) scale to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…With respect to joy, these findings dovetail with a growing literature suggesting mania symptoms involve a heightened focus on the pursuit of rewards and ambitious goals (Alloy & Abramson, 2010; Johnson, 2005; Meyer, Johnson, & Winters, 2001). Importantly in the emerging adolescent literature, these findings are consistent with work among outpatient adolescents suggesting that reward-relevant positive emotions were concurrently associated with increased manic symptom severity (Gruber et al, 2013). This work also is also consistent with research in adults with BPSD suggesting that increased reward sensitivity is concurrently associated with increased manic symptoms, providing encouraging support for developmental continuity in positive associations between reward-relevant emotions and mania symptoms (Alloy & Abramson, 2010; Johnson, 2005; Meyer et al, 2001; Urosevic et al, 2008).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…With respect to joy, these findings dovetail with a growing literature suggesting mania symptoms involve a heightened focus on the pursuit of rewards and ambitious goals (Alloy & Abramson, 2010; Johnson, 2005; Meyer, Johnson, & Winters, 2001). Importantly in the emerging adolescent literature, these findings are consistent with work among outpatient adolescents suggesting that reward-relevant positive emotions were concurrently associated with increased manic symptom severity (Gruber et al, 2013). This work also is also consistent with research in adults with BPSD suggesting that increased reward sensitivity is concurrently associated with increased manic symptoms, providing encouraging support for developmental continuity in positive associations between reward-relevant emotions and mania symptoms (Alloy & Abramson, 2010; Johnson, 2005; Meyer et al, 2001; Urosevic et al, 2008).…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, adolescents at risk for or with depression demonstrate blunted reward responding that is associated with lower levels of daily positive emotion (Forbes et al, 2009) while decreased happiness predicts the onset of depressive symptoms (Neumann, Lier, Frijns, Meeus, & Koot, 2011). Similar to adult literature, adolescent BPSDs are characterized by dysregulated reward learning (Dickstein et al, 2009) and increased reward sensitivity and approach-motivated behaviors being associated with elevated manic symptoms (Gruber et al, 2013). Taken together, elevated reward-seeking positive emotions (such as joy) and increased goal approach-motivated emotions (including anger) appear to be linked to manic and depressive symptoms in adolescents.…”
Section: Positive Emotion and Adolescent Mood Disturbancementioning
confidence: 88%
“…Self-reported high BAS sensitivity also distinguishes BSD patients from those with unipolar depression (Quilty, Mackew, & Bagby, 2014). Similarly, Gruber et al (2013) found that parents’ reports of their adolescent offspring’s BAS sensitivity were associated with both manic and depressive symptoms of those offspring. Thus, BSDs are associated with elevated self-reported reward sensitivity and reward-relevant personality traits.…”
Section: Reward Hypersensitivity In Bipolar Spectrum Disorders: Theormentioning
confidence: 87%
“…Higher BAS sensitivity also distinguished patients with BSD from patients with unipolar depression (Quilty et al, 2014). In addition, parent reports of BAS sensitivity were associated with both manic and depressive symptoms in an outpatient sample of adolescents (Gruber et al, 2013). Even in a euthymic state, individuals with BSDs exhibit higher self-reported BAS sensitivity (Alloy et al, 2008; Salavert et al, 2007), suggesting that the high reward sensitivity may be independent of mood-related report biases.…”
Section: Reward Hypersensitivity Model Of Bipolar Spectrum Disorders:mentioning
confidence: 99%